Analisis Kebutuhan Pengembangan Monopoli Sebagai Media Pembelajaran Pada materi Ekosistem - Zakiyati Salma; Heffi Alberida (LP2M UIN Ambon, 2026)
Learning media is an important component that helps students understand the material and increases learning motivation. However, the use of interesting learning media in ecosystem material is still limited so that students tend to be less active in learning. This condition indicates the need for media development that is appropriate to the needs of teachers and students. This study aims to analyze the need for developing monopoly media as a learning medium for ecosystem material for Phase E of SMA/MA. The study used a descriptive method with a quantitative and qualitative approach. Data collection techniques were carried out through observation, interviews, and needs analysis questionnaires. The results of the interviews showed that students need learning media that can increase learning participation, while teachers need effective media to support learning. The conclusion of this study is the need for monopoly as a learning medium for ecosystem material.